Cosplay the Marvel way : a guide to costuming culture and crafting basics - Stephens, Judith (Running Press, an imprint of Hachette Book Group, Inc., 2024)
"Become part of the Marvel universe with this one-of-a-kind, official guide on how to cosplay as some of your favorite Marvel characters-like Black Panther, Loki, Ms. Marvel, Captain America, Jean Grey, and more-perfect for Marvel fans and cosplayers of all levels"--